Aristotle on agency, habits and institutions. Issue 4 (21st April 2016) - CRESPO, RICARDO F.
Abstract: This paper introduces Aristotle's conception of agency, habits and institutions as a way of contributing to some current discussions about the definition, nature and theory of institutions. Aristotle developed a theory of human action, where we can find a place for 'agency'. His views on habits are linked to his theory of virtue and art (skill). Concerning institutions, Aristotle provides a sound social and political philosophy that encompasses the nature and role of institutions. The paper will subsequently present Aristotle's ideas on these three notions – agency, habits and institutions – and will finally establish which of the current accounts of institutions involved in the discussion sparked by Hindriks and Guala's recent paper (2005a) he would support. Given that some realities tackled in the paper are nowadays radically different from Aristotle's times, the paper tries to keep an 'Aristotelian-minded' point of view – that is, analysing current topics based on Aristotelian concepts.